Velocity of small-scale auroral ionospheric current systems over Indian Antarctic station Maitri - Rajaram, G.; Hanchinal, A.N.; Kalra, R.; Nair, K.U.; Jeeva, K.; Sridharan, M.; Dhar, Ajay (My University, 2002)
The Indian Antarctic station Maitri (geog. 70‡45’S, 11‡45’E, geom. 66‡.03S, 53‡.21E) occupies a sub-auroral location during magnetically quiet conditions(Σκρ < 10), but attains an auroral position when the auroral oval shifts equatorwards with increasing strength of magnetic disturbance. At the latter times, triangulation with 3 fluxgate magnetometers located at the vertices of a suitable triangle provides a means of monitoring mobile auroral ionospheric current systems over Maitri. The spacing between the magnetometers is typically kept at 75–200 km, keeping in mind the scale-sizes of ∼ 100 km for these mobile current systems. This work reports the results of two triangulation experiments carried out around Maitri in January 1992 and January 1995, both during Antarctic summer. The velocities estimated for pulsations of the Pc4 and Pc5 type were about 0.59 km/sec in the direction 102‡.7 east of due north, in the first case, and about 1–3 km/sec in the second case in the east-west direction. While several magnetometer arrays exist in the northern auroral regions (e.g., the Alberta array in Canada, the Alaskan array in the U.S. and the IMS Scandinavian array), there is no report in literature of triangulation through arrays in Antarctica, except for a one-day study by Neudegget al 1995 for ULF pulsations of the Pc1 and Pc2 type. The velocities obtained for the Pi3 type of irregular pulsations over Antarctica in the present study tally well with those obtained for northern auroral locations.
Keywords: Small-scale auroral; Indian Antarctic station; Maitri; Magnetometers; Northern auroral regions; Geomagnetic pulsations; Mobile auroral current systems; Field-aligned currents